Ensigeropus, a new genus of the family Platyischnopidae (Amphipoda: Amphilochidea) from Northern Chile - Pérez-Schultheiss, Jorge (Zootaxa, 2017)
A new genus and species of Platyischnopidae from the sandy intertidal of two localities in the north of Chile are described. Ensigeropus cachinalito n. gen., n. sp. is similar to Eudevenopus Thomas & Barnard, 1983 in most characters; however, it presents characters hitherto not reported in the family, as the lobate upper lip and the absence of a mandibular molar. The new taxon is easily recognized among all American Platyischnopidae by the presence of a conspicuous tooth on the posterior margin of the basis of pereopod 7, a character present also in species of the Australian genus Tomituka Barnard & Drummond, 1979.